2008
DOI: 10.1128/jb.01147-07
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of l -Lactate Utilization by the FadR-Type Regulator LldR of Corynebacterium glutamicum

Abstract: Corynebacterium glutamicum can grow on L-lactate as a sole carbon and energy source. The NCgl2816-lldD operon encoding a putative transporter (NCgl2816) and a quinone-dependent L-lactate dehydrogenase (LldD) is required for L-lactate utilization. DNA affinity chromatography revealed that the FadR-type regulator LldR (encoded by NCgl2814) binds to the upstream region of NCgl2816-lldD. Overexpression of lldR resulted in strongly reduced NCgl2816-lldD mRNA levels and strongly reduced LldD activity, and as a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(81 citation statements)
references
References 55 publications
1
79
1
Order By: Relevance
“…4a). It was also reported that overexpression and deletion of lldR have no significant effects on growth rate or biomass formation compared to WT in minimal medium containing glucose as a sole carbon source (Georgi et al, 2008). In the lldR disruptant strain, glutamate production was slightly increased reproducibly, although it was not significant statistically.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…4a). It was also reported that overexpression and deletion of lldR have no significant effects on growth rate or biomass formation compared to WT in minimal medium containing glucose as a sole carbon source (Georgi et al, 2008). In the lldR disruptant strain, glutamate production was slightly increased reproducibly, although it was not significant statistically.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, LldR also represses the fruR-fruk-ptsF operon responsible for fructose utilization (Gao et al, 2008). It was reported that overexpression of lldR resulted in a decrease in expression of ldhA and the NCgl2816-lldD operon, while disruption of lldR showed a significant increase in expression of the NCgl2816-lldD operon (Gao et al, 2008;Georgi et al, 2008). Disruption of lldR showed a significant increase in ldhA expression in the absence of sugar (Gao et al, 2008) and showed no significant change in ldhA expression in the presence of sugar (Georgi et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FadR regulators are the most abundant amongst the GntR family of transcription regulators and consist of all a-helical C-terminal domains with a mean length of~160 aa (Haydon & Guest, 1991;Rigali et al, 2002;Vindal et al, 2007a, b). Extensive studies have been carried on the FadRs of Escherichia coli, Vibrio vulnificus and Corynebacterium glutamicum, and they are reported to play important roles both in cellular physiology and virulence (Agari et al, 2011;Brown & Gulig, 2008;Casali et al, 2006;Georgi et al, 2008;Santangelo et al, 2008). However, current knowledge on the promoter architecture and regulation of these FadR-like proteins in mycobacteria is limited.…”
Section: Introductionmentioning
confidence: 99%
“…An imperfect inverted repeat sequence 59-TNGT-N 3 -ACNA-39 can serve as an operator for the LldR repressor (Gao et al, 2008;Georgi et al, 2008). The lutABC operon of the undomesticated strain NCIB 3610 of B. subtilis encodes three iron-sulfur-containing proteins responsible for L-lactate utilization (Chai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%